Patterns of participation in the Grow parenting program. Issue 1 (18th March 2019) - Czymoniewicz-Klippel, Melina; Chesnut, Ryan; DiNallo, Jennifer; Perkins, Daniel
Abstract : Purpose: Employing brief, low-intensity, face-to-face parenting programs can result in improvements in parenting and child behavior; however, their usefulness is often limited by low participation rates. Online technologies are increasingly presented as a panacea for promoting program reach in a cost-effective way. The extant literature, however, provides limited guidance on issues around the implementation of online parenting programs. Grow is a universal, health-promoting parenting program that targets families with 5–10 year olds and was developed for face-to-face delivery and then adapted for a web-based format. The purpose of this paper is to present implementation results from feasibility proof of concept studies of Grow Face-to-Face and Grow Online and explores issues regarding mode of delivery and parent participation. Design/methodology/approach: Data were gathered from participants using attendance records, end-of-module/session surveys and semi-structured, in-depth interviews, and were examined using descriptive statistics and inductive thematic analysis. Findings: Findings suggest that, compared to the online implementation, recruitment was more difficult for the face-to-face implementation. Conversely, retention in the online program was poorer than in the face-to-face program. Participants from both programs self-reported high levels of engagement and satisfaction. Parents who completed Grow Online expressed a desire for more interpersonal interactions, which suggests a possible need for hybrid programs that combine online technologies with traditional face-to-face modes of delivery. Originality/value: These findings challenge the idea that the internet can fully address barriers to parenting program participation by showing that while parents may sign up more readily for an online program, they may struggle to complete all modules. This is problematic as program dosage can influence parent and child outcomes.